Prevalence and exploration of HIV pre-exposure prophylaxis awareness in men who have sex with men aged 18–29 years in Lima, Peru, during 2021: A mixed methods study - Tofeño, Diego (2025)
Introduction: Pre-exposure prophylaxis (PrEP) is a therapeutic scheme that has shown effectiveness in reducing the risk of HIV infection through sexual contact. PrEP has been used in various countries globally and in Latin America as a public health measure. In Peru, the greatest increase in HIV incidence in recent years has occurred in the age group of 20–29 years and 15–19 years, this being an important range to be able to implement prevention measures. Objectives: To determine the prevalence of awareness of HIV PrEP and to explore the knowledge and attitudes regarding its use among men who have sex with men (MSM) aged 18–29 years in Lima, Peru. Methods: Explanatory sequential mixed method study whose central component is quantitative. A survey (non-probabilistic descriptive cross-sectional) and a virtual interview (phenomenological approach) were used for data collection. Results: Of 100 seronegative MSM surveyed, 49 % were aware of PrEP. In the qualitative component, it was found that most participants obtained information casually through their social networks. It was also found that they had significant concern about the adverse effects of PrEP, which was mentioned as a barrier to its use. Conclusion: Almost half of MSM are aware of the existence of PrEP, a medication that helps prevent HIV. However, it is important to find more reliable sources of information about PrEP because the fear of adverse effects and ignorance about it are limitations to its consumption.